Культура речевой коммуникации как учебная дисциплина в системе полиязычного образования Республики Казахстан - Кондубаева, Мариам (Studia Rossica Posnaniensia, 2014)
This article describes the connections between the culture of linguistic communication and the other areas of linguistics in the system of education at universities in Kazakhstan.